ANALISIS PERAN PEREMPUAN DALAM PARTAI POLITIK DI DEWAN PIMPINAN CABANG PARTAI DEMOKRASI INDONESIA PERJUANGAN (DPC PDI P) KOTA CIREBON - Malik, Yogi M; Astuti, Puji; Marlina, Neny (Journal of Politic and Government Studies, 2016)
issue of gender is an issue that since the agreement had been made both in Indonesia andin other countries, in essence the issue of gender is an issue that demands for equal rightsbetween men and women, gender is a dominant aspect in politics, in relation class, age group orethnicity. Since 2002 the issue of increasing the number of women to become involved in thepolitical world has begun socialized until finally in the 2004 elections the representation ofwomen in politics has begun to be increased to 30% in Parliament until now.The methodology used in this study is a qualitative research methodology. In thisresearch, data collection techniques used were interviews with sources and literature that supportto this research. The location of research undertaken is at the secretariat office PDI P Cirebon,PDI-P faction Office of Cirebon, and at the homes of volunteers.In this study include two discussion is to see how the role of women in the managementand see how the legislative nomination process that took place whether or not gender responsive.Discussion on the role of women include the level of the role of women in the management cadreof the party, while the discussion on legislative nomination process includes female cadresnomination process flow from the bottom to the top.The conclusion of this study, the first formulation of the vision and mission of theIndonesian Democratic Party of Struggle in general very focused on women because there is nodifference between men and women, the second in response to the policy of affirmative DPPissued a decree mandating the nomination process must include 30% representation of women,this shows that the party is very responsive to the policy, the third in performing its role in worldpolitics cadre of women experience some psychological barriers such as barriers, culturalbarriers, and economic barriers.